Regulasi dan Sanksi Pelanggaran Iklan Televisi di Indonesia: Studi Kasus Iklan Garnier Micellar Water Tahun 2023 - Ahmad Ibrahim; Rizki Agus Nugraha; Denny Wahyudi; Daniel Handoko (Lembaga Pengembangan Kinerja Dosen, 2024)
Advertising is a crucial element in marketing strategies aimed at attracting consumer attention and influencing purchasing decisions. The rapid development of Indonesia's advertising industry, driven by increasing media consumption, has brought about ethical and regulatory challenges. This study examines the ethical violations in the Garnier Micellar Water television advertisement in 2023, which claimed to be the